RecruitPlotEasy: An Advanced Read Recruitment Plot Tool for Assessing Metagenomic Population Abundance and Genetic Diversity - Gerhardt, Kenji; Ruiz-Perez, Carlos A.; Rodriguez-R, Luis M.; Conrad, Roth E.; Konstantinidis, Konstantinos T. (Frontiers in Bioinformatics, 2022)
Mapping of short metagenomic (or metatranscriptomic) read data to reference isolate or single-cell genomes or metagenome-assembled genomes (MAGs) to assess microbial population relative abundance and/or structure represents an essential task of many studies across environmental and clinical settings. Currently, no tool exists for this task, and most researchers use in-house, ad hoc approaches instead. Here, we introduce RecruitPlotEasy, a fully automated, user-friendly pipeline for this purpose. RecruitPlotEasy integrates statistical approaches to quantify intra-population sequence and gene-content diversity and identify co-occurring relative populations in the sample. Hence, RecruitPlotEasy should also greatly facilitate population genetics studies. RecruitPlotEasy is implemented in Python and R languages and is freely available open source software under the Artistic License 2.0 from https://github.com/KGerhardt/RecruitPlotEasy